New species of the genus Epiphragma Osten Sacken from Yunnan, Southwest China (Diptera, Limoniidae) - Mao, Meng; Yang, Ding (Zootaxa, 2009)
The subgenus Epiphragma (Epiphragma) Osten Sacken, 1860 is recorded from Yunnan (Southwest China) for the first time. The following five species with two dark rings on the femora are described as new to science: E. mediale sp. nov., E. yunnanense sp. nov., E. ancistrum sp. nov., E. breve sp. nov. and E. elongatum sp. nov. Their relationships with closely related species are discussed. A key to the species of the subgenus Epiphragma from China is presented for the first time.